PENGGUNAAN JAMBAN TRADISIONAL PADA MASYARAKAT TRANSISI DI SUMATERA SELATAN - Harapan, Edi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Healthy environment requires community participation, through clean water programs and providing healthy latrines for families as places to defecate. The use of traditional latrines is the main cause of pollution of river water and the surrounding air. In the case of river water is a basic requirement for the community. Changing the habit of people defecating in rivers has been carried out by the government through the provision of stimulants in the form of